Acute retinal necrosis: Clinical manifestation and long-term visual outcomes in a series of polymerase chain reaction–positive patients. Issue 4 (July 2021) - Hedayatfar, Alireza; Ebrahimiadib, Nazanin; Zarei, Mohammad; Ashraf Khorasani, Maryam; Mahbod, Mirgholamreza; Asgari, Soheila; Sedaghat, Ahad
Purpose: To report the clinical spectrum, viral etiologies, therapeutic interventions, timing of rhegmatogenous retinal detachments (RRD), and visual outcomes in acute retinal necrosis (ARN) syndrome in a series of polymerase chain reaction (PCR)-positive eyes. Methods: From January 2010 to January 2017, consecutive patients with the clinical diagnosis of ARN and a positive aqueous viral PCR were included in this observational, retrospective study. Results: Nineteen eyes found to have a clinical diagnosis of ARN, of which 18 (94.7%) had a positive viral PCR. ARN was unilateral, except in one patient. None of the fellow eyes manifested ARN during follow-up. Varicella-zoster virus (VZV) was detected in 78.0% of ARN eyes. 61.1% of eyes experienced RRD. The median time for the occurrence of RRD was 12 weeks (range: 6–25 weeks) after disease onset. No correlation was found between the etiologic viral agent (VZV vs non-VZV; p  = 1.000), extent of retinitis (1–2 quadrant vs 3–4 quadrants; p  = 0.326), administration of intravitreal ganciclovir (injected vs not injected; p  = 0.332), application of prophylactic laser retinopexy (applied vs not applied; p  = 0.326), and subsequent occurrence of RRD. At a 2-year follow-up, visual impairment (VA ⩽ 20/200) and severe visual loss (VA ⩽ light perception) were significantly higher in those complicated by RRD compared to non-RRD eyes (81.8% vs 28.6%; p  = 0.047, and 45.4% vs 0.0%; p  = 0.004, respectively). Conclusion: Aqueous PCR results are highly consistent with the clinical diagnosis of ARN. Regardless of the method of management, the rate of RRD is high and is associated with a poor visual outcome.